Comparative study of biochemical health markers, in two groups of university professors of the same age group, 2017 - Domínguez Navarrete, Nicanor (2019)
Objective: Compare the values of the blood biomakers: uric acid, creatinine, glucose, cholesterol and triglycerides, in two groups of university professors apparently healthy. Methods: The first group, formed by 58 professors aged 60 to 64, and the second formed by 35 professors aged 75 to 81, in order to evaluate if there is a significant statistic difference in both groups. Results: The values of uric acid in group I were between 2,50 mg/dL. and 8,20 mg/dL; in groups II were between 2,50 mg/dL and 8,63 mg/dL, showing a significant difference (p=0.035). The values of creatinine in group I were between 0,64 mg/dL and 1,56 mg/dL; and in group II were between 0,80 mg/dL and 1,61 mg/dL., showing a significant difference (p=0.004). The values of glucose in group I were between 63 mg/dL and 188 mg/dL; and in group II were between 60 mg/dL y 297 mg/dL, not showing significant difference (p=0.671). The values of cholesterol in group I were between 125 mg/dL and 265 mg/dL; and in group II were between 107 mg/dL and 244 mg/dL; not showing significant difference (p=0.053). The values of triglycerides in group I were between 58 mg/dL and 507 mg/dL; and in group II were between 68 mg/dL and 314 mg/dL; not showing significant difference (p=0.104). Conclusion: There is a significant difference in the biomarkers of uric acid and creatinine between the age groups; however, there was not found significant difference in the biomarkers of glucose, cholesterol and triglycerides between the age groups. DOI:10.25176/RFMH.v19.n2.2063